2012
DOI: 10.3390/app2020396
|View full text |Cite
|
Sign up to set email alerts
|

Ion Beam Formation and Modification of Cobalt Nanoparticles

Abstract: This article reviews the size-dependent structural properties of ion beam synthesized Co nanoparticles (NPs) and the influence of ion irradiation on the size, shape, phase and structure. The evolution of the aforementioned properties were determined using complementary laboratory-and advanced synchrotron-based techniques, including cross-sectional transmission electron microscopy, small-angle X-ray scattering and X-ray absorption spectroscopy. Combining such techniques reveals a rich array of transformations p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 127 publications
1
16
0
Order By: Relevance
“…In the EXAFS, the intensity of the Mn-Mn peak, associated with the Mn metal with a shorter bond length than that of the bulk Mn metal, is increased. Bond length shrinkage is one of the observed structural changes as the nanoparticle size decreases compared to the bulk standard [63][64][65][66][67]. Because all surfaces are energetically unfavorable compared to the bulk side, the surface energy is reduced by altering the atomic geometry of the local surface by relaxation/reconstruction, which shortens the bond length [64,68].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the EXAFS, the intensity of the Mn-Mn peak, associated with the Mn metal with a shorter bond length than that of the bulk Mn metal, is increased. Bond length shrinkage is one of the observed structural changes as the nanoparticle size decreases compared to the bulk standard [63][64][65][66][67]. Because all surfaces are energetically unfavorable compared to the bulk side, the surface energy is reduced by altering the atomic geometry of the local surface by relaxation/reconstruction, which shortens the bond length [64,68].…”
Section: Resultsmentioning
confidence: 99%
“…Because all surfaces are energetically unfavorable compared to the bulk side, the surface energy is reduced by altering the atomic geometry of the local surface by relaxation/reconstruction, which shortens the bond length [64,68]. The increasing Mn metal peak intensity in the slope region is associated with the reduction of the remaining highly disordered manganese oxide [60] and the clustering by packing between the highly disordered Mn metal nanoparticles with large surface-to-volume ratios [65,67]. Based on previous reports, the capacity in this slope region is attributed to the formation of an electrolyte-derived surface layer, known as the SEI [46][47][48][49] and polymer gel-like film [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…Further, as also discussed in Ref. [26], on heating the phase transformation from hcp to fcc is generally complete, whereas the fcc-to-hcp transformation on cooling is generally only partial, in line with very recent theoretical studies of the effect of cooling rates on the microstructural evolution of nanocrystalline Co [31]. In the context of these studies the pressure, heating/cooling rate, grain size, and impurities have been identified as sources of the differing results regarding phase transformations [26,28,31].…”
Section: Introductionmentioning
confidence: 67%
“…The crystal structure of Co nanoparticles at room temperature has been demonstrated to depend on the synthesis route and processing history of the sample due to almost isoenergetic crystal phases [26]. Apart from the metastable phase produced by the above-mentioned solution-phase synthesis route, for small nanoparticles (<20 nm) the fcc structure appears to be favored at room temperature in nanoparticles created by sputtering, with mixed-phases observed for mediumsized particles (30-40 nm) and hcp structure for large-size particles (>40 nm) [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation